Pancreatic cancer surgery in elderly patients: Balancing between short-term harm and long-term benefit. A population-based study in the Netherlands. (3rd March 2016) - van der Geest, Lydia G. M.; Besselink, Marc G. H.; van Gestel, Yvette R. B. M.; Busch, Olivier R. C.; de Hingh, Ignace H. J. T.; de Jong, Koert P.; Molenaar, I. Quintus; Lemmens, Valery E. P. P.
Abstract: Background : At a national level, it is unknown to what degree elderly patients with pancreatic or periampullary carcinoma benefit from surgical treatment compared to their younger counterparts. We investigated resection rates and outcomes after surgical treatment among elderly patients. Methods : From the Netherlands Cancer Registry, 20 005 patients diagnosed with primary pancreatic or periampullary cancer in 2005–2013 were selected. The associations between age (<70, 70–74, 75–79,  ≥80 years) and resection rates were investigated using χ 2 tests, and surgical outcomes (30-, 90-day mortality) were evaluated using logistic regression analysis. Overall survival after resection was investigated by means of Kaplan-Meier and Cox proportional hazard regression analysis. Results : During the study period, resection rates increased in all age groups (<70 years: 20–30%, p  < 0.001; ≥80 years: 2–8%, p  < 0.001). Of 3845 patients who underwent tumour resection for pancreatic or periampullary carcinoma, the proportion of octogenarians increased from 3.5% to 5.5% (p = 0.03), whereas postoperative mortality did not increase (30-day: 6–3%, p = 0.06; 90-day: 9–8%, p = 0.21). With rising age, 30-day postoperative mortality increased (4–5–7–8%, respectively, p  < 0.001), while 90-day mortality was 6–10–13–12% ( p  < 0.001) and three-year overall survival rates after surgery were 35–33–28–31%, respectively ( p  < 0.001). After adjustment for confounding factors, octogenarians who survived 90 days postoperative exhibited an overall survival close to younger patients [hazard ratio (≥80 vs. <70 years) = 1.21, 95% confidence interval (0.99–1.47), p = 0.07]. Conclusion : Despite higher short-term mortality, octogenarians who underwent pancreatic resection showed long-term survival similar to younger patients. With careful patient screening and counselling of elderly patients, a further increase of resection rates may be combined with improved outcomes.